2020
DOI: 10.1155/2020/1937387
|View full text |Cite
|
Sign up to set email alerts
|

Protein Level and Infantile Diarrhea in a Postweaning Piglet Model

Abstract: Infantile diarrhea is a serious public health problem around worldwide and results in millions of deaths each year. The levels and sources of dietary protein are potential sources of diarrhea, but the relationship between the pathogenesis causes of infantile diarrhea and protein intake remains poorly understood. Many studies have indicated that the key to understanding the relationship between the protein in the diet and the postweaning diarrhea of piglets is to explore the influences of protein sources and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 59 publications
2
19
1
1
Order By: Relevance
“…Our study showed that VH, VW, VH:CD ratio, and the villous surface area of the ileum narrowed under treatment with HP, which is in accordance with piglets’ intestinal mucosa being more easily damaged when fed a high CP ( van Beers-Schreurs et al., 1998 ; Wu et al., 2017 ), thus resulting in poor growth performance. A previous study demonstrated that CD was increased when pigs were fed with higher protein levels ( Gao et al., 2020 ), conflicting with our finding that dietary HP decreased colonic CD, which could be because that research focused more on the ileum, while the change appeared in the colon in our study. Crypt depth may be dependent on the proliferation and shedding rate of epithelial cells ( Hampson, 1986 ; Williams et al., 2013 ); however, more experiments are needed to further elucidate this notion.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed that VH, VW, VH:CD ratio, and the villous surface area of the ileum narrowed under treatment with HP, which is in accordance with piglets’ intestinal mucosa being more easily damaged when fed a high CP ( van Beers-Schreurs et al., 1998 ; Wu et al., 2017 ), thus resulting in poor growth performance. A previous study demonstrated that CD was increased when pigs were fed with higher protein levels ( Gao et al., 2020 ), conflicting with our finding that dietary HP decreased colonic CD, which could be because that research focused more on the ileum, while the change appeared in the colon in our study. Crypt depth may be dependent on the proliferation and shedding rate of epithelial cells ( Hampson, 1986 ; Williams et al., 2013 ); however, more experiments are needed to further elucidate this notion.…”
Section: Discussioncontrasting
confidence: 99%
“…The diets we mixed in this experiment were described in our previous study [ 11 ]. The diets were free of antibiotics and growth enhancers, and they met or surpassed NRC standards for all essential amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…Protein is an indispensable nutrient for the growth of piglets, but piglets are very sensitive to crude protein (CP) levels. Lower CP levels reduce villus height and crypt depth in the small intestine, affect the balance of microbiota, decrease the digestion and utilization of proteins in the intestine, and decrease the growth performance of piglets (Luo et al, 2015;Peng et al, 2016Peng et al, , 2017, whereas excessive CP levels result in a large amount of undigested and utilized proteins entering the intestine and fermenting spoilage and increase the pH in the stomach and small intestine, thereby providing suitable conditions for colonization of the intestine by pathogens and disrupting the balance of intestinal bacteria, leading to diarrhea (Gao et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At present, diarrheal disease has been the cause of high mortality in children (Liu et al., 2019; Taborda et al., 2018). How to control infant diarrhea by regulating the level of protein has been a focus of recent research (Gao et al., 2020). The piglet model has become the best model for human nutrition.…”
Section: Introductionmentioning
confidence: 99%